PENGARUH KARAKTERISTIK SISTEM INFORMASI AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL PADA BPR DI KOTA BANDAR LAMPUNG - anggun novita sari; Reni Oktavia; Pigo Nauli (Jurnal Akuntansi dan Keuangan (JAK), 2020)
BPR face difficulties with the high ratio of non-performing loans and competition for peer-to-peer landing online or financial technology (fintech) which was published in CNBC Indonesia. To survive in the sphere of intense business competition, where in the future there will be many digital economic developments, the emergence of products that are increasingly integrated in various financial companies, business must be able to create flexible and innovative business conditions, and must also consider external factors of their business. It must also be followed by technological developments in order to survive and be able to compete in global competition. The high competitiveness created by a business actor can be achieved in one way, which is by increasing managerial performance. This study aims to analyze the influence of the characteristics of management accounting information systems on the managerial performance of rural banks. This study uses primary data using a survey method by giving questionnaires to operational managers of BPR in the city of Bandar Lampung. Based on the research results, it is known that broadscape, timeliness, aggregation, integration significantly and positively affect managerial performance